DESIGN OF A COMPLEX OF MEDICAL SERVICE ROBOTS AND ANALYSIS OF TRANSMISSION CHARACTERISTICS OF DRIVES - Seidakhmet, Askar; Tuleshov, Amandyk; Jamalov, Nutpulla; Koshekov, Kairat; Abduraimov, Azizbek; Kamal, Aziz; Kanapiya, Magzhan; Gritsenko, Igor; Kaliyev, Madi; Largin, Alexandr; Zhauyt, Algazy (Journal of Applied Engineering Science, 2022)
The article describes a complex of robots designed and manufactured at the Institute of Mechanics and Machine Science for a hospital environment, consisting of a transport robot and two functional robots: assistant robot and a disinfection robot. The assistant robot is designed to measure temperature and blood pressure, automate the transportation of medicines, bed linen, food, etc. using a transport robot. With the help of a scissor mechanism the assistant robot is able to adjust the height of the trays, devices for measuring temperature and blood pressure. The disinfection robot is designed to automate disinfection in enclosed spaces. UV lamps with rotating 180 degrees reflectors, allow the disinfection robot to work in two modes: direct irradiation of the room with ultraviolet light and air recycling. There is also a mode of spraying disinfectant liquid. The article describes the design of a transport robot, an assistant robot and a disinfection robot, and shows the results of experimental studies.